Silica-Supported Sulfuric Acid as Doping Agent in Synthesis of a New Composite of Poly(o-methoxyaniline) Under Solid-State Condition - Modarresi-Alam, Ali Reza; Shariati, Ilnaz (Journal of Basic & Applied Sciences, 2021)
The objective of this research is the synthesis and characterization of the novel composite of poly(o-methoxyaniline)/silica-supported sulfuric acid (POMA-SSSA). The synthesis is done by doping of poly (o-methoxyaniline) emeraldine base in the presence of silica-supported sulfuric acid (SiO2-H2SO4, SSSA) under solid-state (solvent-free) conditions. Herein, poly(o-methoxyaniline) emeraldine salt (POMA-SA) is prepared simply by mixing the base form with H2SO4 in solid-state. The doping process is verified by ultraviolet-visible, Fourier transform infrared spectroscopy and elemental analysis. It is shown that the polymers and composites have maximum doping and the doping counter ion in POMA-SA and POMA-SSSA-bw (before work-up) is HSO4– and in the POMA-SSSA-aw (after work-up) is SO42-. The prepared composites show good conductivity. Scanning electron microscopy (SEM) images show that POMA molecules thoroughly have coated the surface of silica. Moreover, the morphology studies of composites show a smooth surface and sheet-like layer that have covered the particles within the range of 0.5 to 1 μm.